2020
DOI: 10.3389/fpsyg.2020.583174
|View full text |Cite
|
Sign up to set email alerts
|

Viewing Fantastical Events in Animated Television Shows: Immediate Effects on Chinese Preschoolers’ Executive Function

Abstract: Three experiments were conducted to test whether watching an animated show with frequent fantastical events decreased Chinese preschoolers’ post-viewing executive function (EF), and to test possible mechanisms of this effect. In all three experiments, children were randomly assigned to watch a video with either frequent or infrequent fantastical events; their EF was immediately assessed after viewing, using behavioral measures of working memory, sustained attention, and cognitive flexibility. Parents completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 80 publications
(115 reference statements)
0
13
0
Order By: Relevance
“…Animated films positively affect a child's involvement in symbolic mediation and the level of arbitrary behavior [ 54 ]. Also, it was observed that the executive functions of the preschoolers were disrupted after watching the animated fantastical events [ 28 ]. A significant effect of animated features in ebooks (motion and sound) was observed on children's vocabulary acquisition, story retelling, and visual attention [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animated films positively affect a child's involvement in symbolic mediation and the level of arbitrary behavior [ 54 ]. Also, it was observed that the executive functions of the preschoolers were disrupted after watching the animated fantastical events [ 28 ]. A significant effect of animated features in ebooks (motion and sound) was observed on children's vocabulary acquisition, story retelling, and visual attention [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Any fault with these devices will affect the data quality, data loss, and data interpretation bias. Li et al [ 28 ] have suggested that fixation data points showed the preschooler's more significant mobilization and limited processing capacity. Tummeltshammer et al [ 34 ] have determined the unfiltered eye movement data using SMI's BeGaze analysis software to overcome the error caused by the tracking device or participants in attention.…”
Section: Challenges and Open Issuesmentioning
confidence: 99%
“…Physically impossible and hence fantastical events are commonly used in child-directed TV and videos. Comprehension of fantastical events may be cognitively taxing due to their novelty and rarity in daily life, resulting in excessive consumption of resources [115][116][117]. It has been suggested that executive functions and processing fantastical events may rely on the same cognitive resources; thus, watching fantastical events may have immediate negative effects on executive functioning (e.g., [118]).…”
Section: Fantastical Contentmentioning
confidence: 99%
“…It has been suggested that executive functions and processing fantastical events may rely on the same cognitive resources; thus, watching fantastical events may have immediate negative effects on executive functioning (e.g., [118]). To test this hypothesis, a series of studies investigated the short-term effects of watching fantastical content on young children's executive functions and reported poorer performance on executive function tasks after watching fantastical events [115][116][117]119]. These findings were complemented by higher activation of the brain and frequent and shorter eye fixations while watching a higher number of fantastical events, potentially indicating more cognitive effort [116].…”
Section: Fantastical Contentmentioning
confidence: 99%
“…The use of screens at home is part of the daily lives of families in the contemporary context (Strasburger 2015 ; Guedes et al 2019 ; Nobre et al 2021 ); however, evidence indicates that using some criteria is essential to favor child development (Nobre et al 2020 ). Excessive television exposure is associated with delays, for example, in language development (Valdivia Álvarez et al 2014 ; Duch et al 2013 ) and poorer performance on behavioral measures of executive function (EF) (Li et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%